Variants in the SOX9 transactivation middle domain induce axial skeleton dysplasia and scoliosis - Zhaoyang Liu; Valeria Aceves; Hong Colleen Feng; Fangzhou Bian; Jingyu He; Christina J. Song; Benjamin Troutwine; Samuel Ma; Suomao Yuan; Xiaoxin Li; Xinyu Liu; Terry Jianguo Zhang; et al. (Proceedings of the National Academy of Sciences, 2025)
SOX9 is a crucial transcriptional regulator of cartilage development and homeostasis. Dysregulation of SOX9 is associated with a wide spectrum of skeletal disorders, including campomelic dysplasia, acampomelic campomelic dysplasia, and scoliosis. Yet how SOX9 variants contribute to the spectrum of axial skeletal disorders is not well understood. Here, we report four pathogenic variants of SOX9 identified in a cohort of patients with congenital vertebral malformations. We report a pathogenic missense variant in the transactivation middle (TAM) domain of SOX9 associated with mild skeletal dysplasia and scoliosis. We isolated a Sox9 mutant mouse with an in-frame microdeletion in the TAM domain ( Sox9 Asp272del ), which exhibits skeletal dysplasia including kinked tails, rib cage anomalies, and scoliosis in homozygous mutants. We find that both the human missense and the mouse microdeletion mutations resulted in reduced SOX9 protein stability in cell culture, while Sox9 Asp272del mutant mice show decreased SOX9 expression in the growth plate and annulus fibrosus tissues of the spine. This reduction in SOX9 expression was correlated with the reduction of extracellular matrix components, such as tenascin-X and the Adhesion G-protein coupled receptor ADGRG6. In summary, our work identified and modeled a pathologic variant of SOX9 within the TAM domain and demonstrated its importance for SOX9 protein stability. Our work demonstrates that SOX9 stability is important for the regulation of ADGRG6 expression, which is a known regulator of postnatal spine homeostasis, underscoring the essential role of SOX9 dosage in a spectrum of axial skeleton dysplasia in humans.